HOLTER ECG MONITORING AND HEART RATE VARIABILITY IN BREAST CANCER PATIENTS - Mehraliev, O.Sh. (World of Medicine and Biology, 2021)
When establishing indications for Holter ECG monitoring in 115 breast cancer patients, the criteria of the American Heart Association were used. The survey was carried out using the official versions of the EORTC QLQ-C30 questionnaires (a questionnaire approved by the European Organization for Research and Treatment of Cancer in 2005). The most common malignant neoplasms in the main group and in the control group were found in the upper quadrants of the mammary glands. Less often, the pathological process in both groups was diagnosed at the border of the inner quadrants. Compared with the control group, in the main group, the average 24 hours, average daily and average night heart rate was higher (p=0.001). Also in the control group, an increase in the maximum daily heart rate was revealed – here is the average dash. non-hyphenated 115.7±0.85 beats/min, versus 97.7±0.63 beats/min in the main group (p=0.001). When diagnosing metastatic lesions of lymph nodes, there is an increase in (corrected recovery time of sinus node function after AF paroxysm). Against the background of the lesion of regional lymph nodes, the minimum time interval of arousal by AV (P1-R1 min) increases by 152.6±1.08 ms, versus 138.4±1.18 ms, values recorded in the control group (p=0.001). The highest rates were recorded for two profiles “Pain” and “Fatigue” in the main group of patients burdened with metastases to regional lymph nodes (25.9±2.88 points and 44.2±1.78 points, p=0.001; 9.0±1.43 and 26.7±1.29, p=0.001, in the control and main groups, respectively). Thus, the best indicators in the control group are associated with the absence of serious complications of breast cancer, represented by metastatic lesions of the lymphatic system.